The Effect of Brand Image and Medical Quality on Intention of Re-visit with Word of Mouth as a Mediating Variable among Patients - Irdan, Irdan; Kusumapradja, Rokiah; Ramadhan, Yanuar (International Journal of Nursing and Health Services (IJNHS), 2024)
Background: People with different characteristics are very selective in choosing hospital health services. People would select the hospital with modern, best medical facilities and trained doctors who offer high-quality services consistently. However, having a successful hospital and able to attract patients back is difficult, especially in the context of limited relevant literature. Objective: This study aimed to analyze the effect of brand image and perceived medical quality on intention of re-visit with word of mouth as mediation variable among patients in Sari Asih Cipondoh Hospital, Tangerang. Method: We conduct the cross-sectional study to examine the causalities of independent variable with dependent variable. One hundred seventy-five patients were recruited in this study especially those who have visit the hospital at least once within two year. The Structural Equation Modeling (SEM) using Partial Least Square (PLS) approach was applied to analyze the data. Result: The results showed that brand image and perceived medical quality had a positive influence on word of mouth and the intention to hospital re-visit and word of mouth had an impact on the intentions to re-visit hospital. Implication: A good hospital brand image perception is enough for the patient to encourage the intention to visit again. Medical quality is considered important to hospitals, as patients can enjoy it immediately, especially in increasing the intention to visit again. In addition, patients will be more confident to use health care if word of mouth is high